HUBUNGAN PERENCANAAN OLEH CAMAT DENGAN EFEKTIVITAS PENCAPAIAN TARGET PAJAK BUMI DAN BANGUNAN PADA KECAMATAN SINDANG AGUNG KABUPATEN KUNINGAN - nana Sumarna; Hery Nariyah; Idih Machmud (Jurnal Ilmiah Publika, 2013)
Title research is “Plenning Relationships By Head to the effectiveness of AchievementTargets Land and Building Tax in the District Brass Brass District”.The problem that the author found is the effectiveness of the achievement of the land andbuilding tax in the district brass brass district allegedly not been achieved due to non optimalplanning. The research question the authors ask is there a relationship between planning and theeffectiveness of the UN tax target target in sub District Brass Brass.The hypothesis that the author propose is “There is significant relationship betweenplanning and effectiveness in the achievement of the UN Sub District Brass Brass. Methods usedby the writer is a survey method with the quantitative analysis techniques, the study analyzes thevariables supported by the data using statistical formulas. The research proves that the Head ofplanning variables in achieving the UN target of optimal yet reached the stage where enoegh newsuccess with a total score of 859 or 59.7%. In quality it is visible from less optimalimplementation planning steps. Then variabeel effectiveness in the achievement of the UN SubDistrict Brass Brass is also still at levels sufficient or not optimal with a total score of 471 or69.9%.The relationship between the effectiveness of planning variables by Head to theeffectiveness of the effectiveness of the United Nations in the Distric of Guning Jati Cirebonregency high enough to count the value of rs for rs value of 0.532 compared 0.329 for the tablethen the value is significant. Thus, the authors propose the hypothesis Ha Ho accepted andrejected